Antidepressants have Anti-inflammatory Effects that may be Relevant to Dermatology: A Systematic Review - Shirin Eskeland; Jon Anders Halvorsen; Lars Tanum (Medical Journals Sweden, 2017)
There is increasing evidence of clinically relevant anti-inflammatory effects of monoaminergic antidepressants. PubMed and Ovid databases were searched systematically for the use and efficacy of antidepressants in association with 5 common inflammatory skin disorders: chronic urticaria, psoriasis, atopic dermatitis, other eczema, and alopecia areata. From January 1984 to June 2016, publications included a total of 1,252 dermatological patients in 28 trials or case reports. These unambiguously reported a reduced burden of dermatological symptoms in relation to treatment with antidepressants. Several randomized controlled trials of first-generation antidepressants have been published, while studies of modern antidepressants are usually open-label, yet more informative, regarding patients' characteristics and study procedures. These overall positive findings may indicate a rationale, beyond treating comorbid psychiatric disorders, for the use of antidepressants in dermatology. Further research into modern tolerable antidepressants, including selective serotonin re-uptake inhibitors, mirtazapine and bupropion, is required.